Drag-Reducing Agent for Aqueous Liquid Flowing in Turbulent Mode through Pipelines - Zainab Y. Shnain (Al-Khwarizmi College of Engineering – University of Baghdad, 2014)
In this study, mucilage was extracted from Malabar spinach and tested for drag-reducing properties in aqueous liquids flowing through pipelines. Friction produced by liquids flowing in turbulent mode through pipelines increase power consumption. Drag-reducing agents (DRA) such as polymers, suspended solids and surfactants are used to reduce power losses. There is a demand for natural, biodegradable DRA and mucilage is emerging as an attractive alternative to conventional DRAs. Literature review revealed that very little research has been done on the drag-reducing properties of this mucilage and there is an opportunity to explore the potential applications of mucilage from Malabar spinach. An experimental piping rig was used to study the DR properties of the mucilage on water under the effect of varying pipe dimensions and mucilage concentrations. It is shown that these additives can dramatically reduce friction drag provided that the flow is occurring under turbulent conditions. Experimental results also show that DR increases when the mucilage concentration increases.